Increased actin polymerization and stabilization interferes with neuronal function and survival in the AMPKγ mutant Loechrig. - Mandy Cook; Bonnie J Bolkan; Doris Kretzschmar (PLoS ONE)
loechrig (loe) mutant flies are characterized by progressive neuronal degeneration, behavioral deficits, and early death. The mutation is due to a P-element insertion in the gene for the γ-subunit of the trimeric AMP-activated protein kinase (AMPK) complex, whereby the insertion affects only one of several alternative transcripts encoding a unique neuronal isoform. AMPK is a cellular energy sensor that regulates a plethora of signaling pathways, including cholesterol and isoprenoid synthesis via its downstream target hydroxy-methylglutaryl (HMG)-CoA reductase. We recently showed that loe interferes with isoprenoid synthesis and increases the prenylation and thereby activation of RhoA. During development, RhoA plays an important role in neuronal outgrowth by activating a signaling cascade that regulates actin dynamics. Here we show that the effect of loe/AMPKγ on RhoA prenylation leads to a hyperactivation of this signaling pathway, causing increased phosphorylation of the actin depolymerizating factor cofilin and accumulation of filamentous actin. Furthermore, our results show that the resulting cytoskeletal changes in loe interfere with neuronal growth and disrupt axonal integrity. Surprisingly, these phenotypes were enhanced by expressing the Slingshot (SSH) phosphatase, which during development promotes actin depolymerization by dephosphorylating cofilin. However, our studies suggest that in the adult SSH promotes actin polymerization, supporting in vitro studies using human SSH1 that suggested that SSH can also stabilize and bundle filamentous actin. Together with the observed increase in SSH levels in the loe mutant, our experiments suggest that in mature neurons SSH may function as a stabilization factor for filamentous actin instead of promoting actin depolymerization.